TESTING FLORAL MOTIFS FOR CREATION FOR CHILDREN IN KINDERGARTEN - SEDLACKOVA, Alena; SIMBARTL, Petr (Trends in education, 2022)
This paper addresses themes for the development of fine motor skills in children in kindergarten. It focuses on the importance of fine motor skills in children, which is necessary for their development and when starting primary school. It gives reasons why this needs to be addressed. The aim of the paper is to present our work, which was the creation of several tested themes that focus on the development of fine motor skills. The interest was also in the connection between the complexity and popularity of the themes. These themes were tested and a low-volume book with topics was created on this basis, which was distributed to some kindergartens in the Pilsen region. We wanted to present some interesting themes and activities suitable for kindergartens in accordance with the ``Framework Education Programme for Preschool Education''.
Keywords: decoration; floral motifs; kindergarten; preschool age; development of fine motor skills